2019
DOI: 10.1371/journal.pone.0211668
|View full text |Cite
|
Sign up to set email alerts
|

Neurofeedback training with a low-priced EEG device leads to faster alpha enhancement but shows no effect on cognitive performance: A single-blind, sham-feedback study

Abstract: Introduction Findings of recent studies indicate that it is possible to enhance cognitive capacities of healthy individuals by means of individual upper alpha neurofeedback training (NFT). Although these results are promising, most of this research was conducted based on high-priced EEG systems developed for clinical and research purposes. This study addresses the question whether such effects can also be shown with an easy to use and comparably low-priced Emotiv Epoc EEG headset available for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…The results indicate a positive effect of the alpha NFT on memory. In addition, the control groups of most included studies (9 of 14 WM studies and 4 of 6 EM studies) (1 study with active neurofeedback (Pei et al, 2018), 2 studies with sham neurofeedback (Guez et al, 2014;Xiong et al, 2014), or 8 studies with silent feedback (Escolano et al, 2011;Lecomte and Juhel, 2011;Zoefel et al, 2011;Alekseeva et al, 2012;Reis et al, 2016;Farnia et al, 2017;Gordon et al, 2019;Naas et al, 2019) showed no memory change. Two active control groups showed significant improvement in WM and EM after training (Hsueh et al, 2016;Wei et al, 2017), and the alpha group of the two studies exhibited significant enhancement of WM and EM compared with the active control group.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate a positive effect of the alpha NFT on memory. In addition, the control groups of most included studies (9 of 14 WM studies and 4 of 6 EM studies) (1 study with active neurofeedback (Pei et al, 2018), 2 studies with sham neurofeedback (Guez et al, 2014;Xiong et al, 2014), or 8 studies with silent feedback (Escolano et al, 2011;Lecomte and Juhel, 2011;Zoefel et al, 2011;Alekseeva et al, 2012;Reis et al, 2016;Farnia et al, 2017;Gordon et al, 2019;Naas et al, 2019) showed no memory change. Two active control groups showed significant improvement in WM and EM after training (Hsueh et al, 2016;Wei et al, 2017), and the alpha group of the two studies exhibited significant enhancement of WM and EM compared with the active control group.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, the published results to date are variable. For example, Gadea et al [66] [67][68][69] reported successful voluntary modulation of brain activity (change in the EEG signal) but no effects on the behavior (eg, symptom reduction). Both effects were shown in other studies [70][71][72][73][74].…”
Section: Principal Resultsmentioning
confidence: 99%
“…used EEG-based NFT of sensorimotor rhythm regulation over multiple sessions but did not find evidence for between session neuromodulation [29]. Naas et al [30] used an NF protocol targeting upper alpha band over four training sessions in four days and did not reveal any significantly different positive improvement of the targeted activity between groups over time. In contrast, Beatty [31] showed an increase of the trained alpha activity in the NF group but not in the sham-FB condition during a unique NF session.…”
Section: Introductionmentioning
confidence: 99%
“…However, the neurocognitive mechanisms underlying BCI tasks or NF training (NFT) remain elusive 17,18 . The neuromodulation associated with NFT has already been studied in several contexts [19][20][21] , but this was not yet done in a long-term, multiple-session (12 weeks), sham-controlled design using an ecological reinforcer NF context for both NF and control groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation